Propolis-Enhanced Alginate-Collagen Injectable Hydrogel Crosslinked with Calcium Gluconate for Myocardial Infarction Therapy - Azizah Intan Pangesty; Raajwa Ayudhia Kamila; Audrey Cessnawati Putri Bengu Schlumbergerina; Mohammad Daneth Faizurrizqi; Renanda Wafi Fakhri; Sunarso Sunarso; Myrna Nurlatifah Zakaria; Lutviasari Nuraini; Winda Azwani (International Journal of Technology)
Injectable hydrogel has emerged as a viable therapeutic approach for the non-invasive treatment of myocardial infarction. Numerous natural and synthetic injectable hydrogels have been investigated, although they exhibit a deficiency in cardioprotective characteristics. This work integrated propolis, previously found to possess cardioprotective properties, into an injectable hydrogel. The solution was created by incorporating alginate, collagen, and varying quantities of propolis at 3%, 7%, and 10%. The solution was subsequently crosslinked with calcium gluconate to create a hydrogel. The rheology test demonstrated that jellification occurred at 37°C following the incorporation of 0.5% calcium gluconate, as evidenced by an elevation in storage modulus and a reduction in loss modulus. An increase in calcium gluconate was noted to promote crosslinking while concurrently resulting in a swelling degree of up to 17 times in the produced hydrogel. This phenomenon is ascribed to the favourable water permeability of calcium ions. Conversely, the elevation of propolis diminished the extent of swelling due to the enhancement of density. The elevated concentration of calcium gluconate diminished the degradation rate, but the increased amount of propolis accelerated the breakdown. The antioxidant activity assessed using DPPH assays showed that the percentage of inhibition rose with increasing concentrations of propolis. Ultimately, our study revealed that propolis can be integrated into injectable hydrogels for potential therapeutic therapy of myocardial infarction.